Flipped classroom teaching model with video instruction improves skills in local anesthesia training - Yen-Lin Chen; Yu-Wei Chiu; Chuan-Hang Yu; Yu-Chao Chang; Yi-Tzu Chen (Journal of Dental Sciences, 2024)
Background/purpose: Local anesthesia (LA) training is an essential clinical skill in dental education. However, the traditional teaching method of student-to-student injection has ethical concerns. This study investigated whether a flipped classroom (FC) teaching model with instructional videos improves students' skills in administering LA. Materials and methods: Fourth-year dental students in 2017 (traditional teaching, n = 70) and 2018 (FC model, n = 79) were assessed for their ability to perform an inferior alveolar nerve block and lingual nerve block. The FC group watched pre-recorded videos prior to a hands-on training session. Skills were evaluated using a 24-item checklist converted to letter grades. Perceptions of the FC approach were also surveyed. Results: The FC group showed statistically significantly higher final grades than the traditional teaching group (P < 0.05). Most FC students agreed that the videos improved clarity and learning objectives. Conclusion: The FC teaching model with procedural video instruction improved skills and confidence in administering LA over traditional teaching methods. Videos can be a beneficial supplement in pre-clinical dental training.